Privatizáció és a nevető harmadik - Fogarassy, Gabriella; Szántó, Zoltán (Szociológiai Szemle, 2024)
The study intends to contribute to the clarification of the interpersonal preconditions of privatization processes. Its basic aim si to show, typify, and empirically illustrate the strategic interactions (status-seeking efforts, bargaining and coalition formation processes, rent- and influence-seeking activities, etc.), which - at least partly - could explain the fails or successes of the different privatization attempts. The main emphasis is put on the three-person relations. As a conceptual-theoretical starting point Georg Simmel’s and Theodore Caplow’s classical ideas about triad are summerized, then different three-person interactions are presented, which may substantially influence he course of privatization. The empirical illustration is based on a case study of our research on privatization in Hungary.